Statistical optimization of laccase production by Aspergillus flavus PUF5 through submerged fermentation using agro-waste as cheap substrate - Ghosh, Priyanka; Ghosh, Uma (Acta Biologica Szegediensis, 2017)
The plan of this work was to valorize agro-wastes following statistical approach to the production of laccase enzyme by Aspergillus flavus PUF5 through submerged fermentation process (SmF). The process parameters influencing the enzyme production and initially identified using “one variable at a time (OVAT)” design. Among the variables screened, fermentation temperature, pH of the medium, concentration of yeast extract, and NaCl were found most considerable when waste ribbed gourd peel was used as substrate. The most favorable levels of these significant parameters were determined employing the central composite design (CCD). The goodness of fit of the model was checked by the determination coefficient (R2). The contour plots revealed that the optimal values of the process conditions lie within the range; temperature: 25 °C, pH: 4, yeast extract concentration: 0.3% and NaCl: 0.07%. By using the optimal fermentation medium, the improved laccase production was found to be 15.96 U/ml; this was about 4.6-fold higher than the unoptimized media.